Comparing the Effects of Medical Honey and Stapler on Skin Graft Fixation in Patients With Burn Wounds: A Randomized Clinical Trial - Nematollah Ahangar; Amirhossein Pourebrahimi; Parissa Bagheri Toolaroud; Alale Jarrahi; Mohammad Ebrahim Ghaffari; Mojdeh Esmailzadeh; Alireza Feizkhah; Mohammadreza Mobayen (مجله دانشگاه علوم پزشکی گیلان)
Background One of the applications of honey is in wound healing. A stapler normally connects the skin graft to the underlying bed. Due to its high cost and lack of production in Iran, and causing physical damage to the tissue, an alternative method is needed. Objective This study aims to compare the effects of using medical honey and staplers for skin graft fixation in patients with burn wounds in the north of Iran. Methods In this clinical trial, 80 patients with deep second-degree and third-degree burns less than 40% of total body surface area were included and were randomly divided into two groups of honey (n=40) and stapler (n=40). Demographic information and the percentage of burns were extracted from patients’ medical files. The graft rejection, number of hospitalization days, grafted skin displacement, graft contracture, pain severity, existence of edema or hematoma, itching severity, and infection after grafting were investigated and recorded. Results Of 80 patients, 34 were male (42.5%) and 46 were female (57.5%). The mean age of the patients was 39.29±15.42 years. A significant difference was observed in the mean number of hospitalization days after grafting (P<0.001), incidence of infection, hematoma, edema, and severity of pain and itching (P<0.001), which were lower in the honey group. The graft contracture rate was lower in the stapler group (P<0.001). Graft rejection was not observed in any groups. Conclusion The use of medical honey for skin graft fixation reduces the duration of hospitalization and adverse effects such as pain, itching, edema, hematoma, and infection compared to staplers. This method is as efficient as the routine treatment.